Strengthening Farmer Institutions in Rice Farming: An Interpretive Structural Modeling Approach - Sri Wahyuni Kamaruddin; Zulkifli Zulkifli; Akbar Akbar (Institut Pertanian Bogor, 2025)
The primary issue in farmer institutional management is managerial and financial competency, which impedes the efficacy and sustainability of farm companies. To enable long-term agricultural development, institutions must be strengthened through collaboration. The purpose of this study was to determine the institutional function of farmer institutions in boosting rice farming productivity and to examine a plan for institutional improvement of farmer institutions in rice farming using Interpretive Structural Modeling (ISM). Purposive sampling was utilized to choose 21 farmers and 5 stakeholders from a population of 150 farmers, resulting in a sample size of 26 persons. The data analysis technique utilized was a Likert scale using ISM. The findings revealed that farmer institutions play a positive influence in enhancing rice farming production, particularly in terms of expanding knowledge and market access. Through expanded knowledge, farmer institutions provide training and extension services that focus on current rice farming techniques, fertilizer efficiency, and agricultural technology application. The technique of developing farmer institutions in rice production using ISM analysis is a critical component of resource availability and financial support. This research is prioritized because it has a substantial impact on the success of farming institutions. This study emphasizes the relevance of farmer institutions in ensuring access to resources and financial support to improve rice yield, efficiency, and competitiveness while also supporting farmers' well-being. Keywords: financial support, institutional role, rice farming, strategy